Biobanks on Balance between Private Property and Commons: Patents or Open Data sharing? - De Robbio, Antonella; Corradi, Antonella (JLIS.it, 2010)
The circulation and sharing of contents in biobanks is approached with the study of the normative statutes of these institutions, with careful attention to copyright. Such institutions are an organized set of human biological specimens with diagnostic, therapeutic, and research aims. Since the issue is quite new, their statutes are controversial; moreover, the exploitation of new detections is particularly complicated. The ownership of samples (tissues, cells, organs) and the ownership of the biobank as the entity managing the database is crucial in order to determine any rights on researches that can be patented. The sui generic right in Europe states some rights for the database builder, whom allocates economic resources to organize information. However, the main issue of this kind of databases is related to the quality of the patented object: organic and living material. Regarding this fact, there exist stances for privatizing those biological specimens, while the majority consider models of open data sharing as a more suitable way, considering organic samples as “commons”. The latter tendency seems to predominate, protecting the human body and its genome from economical exploitation, although acknowledging some kinds of profits related to the intellectual property.